2005
DOI: 10.1007/s11179-005-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

Directional sensitivity of the Japanese scallop Mizuhopecten yessoensis and Swift scallop Chlamys swifti to water-borne vibrations

Abstract: Behavioral experiments were conducted on two bivalve species-the Japanese scallop Mizuhopecten yessoensis and the Swift scallop Chlamys swifti -to elucidate the role of their abdominal sense organ (ASO) in directional sensitivity to water-borne vibrations. The thresholds were determined at 140 Hz. Both species displayed the highest sensitivity to vibrations, the source of which was placed above the animal (opposite to the left valve), rostro-dorsally to its vertical axis. Removal of the ASO led to loss of dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…They were less responsive to 832 Hz despite a relatively higher pressure level (166 dBrms re 1 μPa). Using a different approach, Zhadan [ 15 ] studied the role of the abdominal sense organ (ASO) in two pecten species, Mizuopecten yessoensis and Chlamys swifti . He reported that contractions of the mantle velum edge in both species are sensitive to modulated ultrasonic vibrations in the range 30–1000 Hz without any information on applied sound pressure level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were less responsive to 832 Hz despite a relatively higher pressure level (166 dBrms re 1 μPa). Using a different approach, Zhadan [ 15 ] studied the role of the abdominal sense organ (ASO) in two pecten species, Mizuopecten yessoensis and Chlamys swifti . He reported that contractions of the mantle velum edge in both species are sensitive to modulated ultrasonic vibrations in the range 30–1000 Hz without any information on applied sound pressure level.…”
Section: Discussionmentioning
confidence: 99%
“…He demonstrated its ability to detect vibrations produced by the waves and to move up and down along a beach with the rising and falling tides. In 2005, Zhadan [ 15 ] reported that a special organ in pectens, the abdominal sense organ, is sensitive to water vibrations. Finally, in 2015 Roberts et al [ 16 ] studied the sensitivity of the blue mussel, Mytilus edulis , to substrate-borne vibrations and demonstrated their sensitivity in the range of 5–400 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the statocyst nerve caused scallops to lose the ability to control the vertical component of their swimming (47), thus compromising a primary mechanism of predator avoidance. The abdominal sense organ has also been suggested to contribute to predator detection, with the detection of waterborne vibrations originating from above the scallop filling in a blind spot of the visual, tactile, and chemoreceptive systems (48).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their ecological role as a habitat-creating species in estuaries, as well as their economic importance and global demise, we sought to test whether the sounds of oyster reefs could enhance recruitment of larval oysters ( Crassostrea virginica ). The specific sensory mechanism by which invertebrate larvae may detect acoustic stimuli has not been determined, but late-stage larval oysters possess both exterior cilia and statocyst sensory structures ( Kennedy, Newell & Eble, 1996 ), which have been shown to be responsive to acoustic particle motion in other aquatic invertebrates ( Rogers & Cox, 1988 ; Budelmann, 1992 ; Zhadan, 2005 ).…”
Section: Introductionmentioning
confidence: 99%